Enforcing high-level protocols in low-level software - DeLIne, Robert; Fahndrich, Manuel (Proceedings of the 2001 ACM SIGPLAN Conference on Programming Language Design and Implementation (PLDI), 2001)
The reliability of infrastructure software, such as operating systems and web servers, is often hampered by the mismanagement of resources, such as memory and network connections. The Vault programming language allows a programmer to describe resource management protocols that the compiler can statically enforce. Such a protocol can specify that operations must be performed in a certain order and that certain operations must be performed before accessing a given data object. Furthermore, Vault enforces statically that resources cannot be leaked. We validate the utility of our approach by enforcing protocols present in the interface between the Windows 2000 kernel and its device drivers.